Critical Appraisal of Emergency Medicine Educational Research: The Best Publications of 2011. (13th February 2013) - Fisher, Jonathan; Lin, Michelle; Coates, Wendy C.; Kuhn, Gloria J.; Farrell, Susan E.; Maggio, Lauren A.; Shayne, Philip; Cone, David C.
Abstract Objectives The objective was to critically appraise and highlight medical education research studies published in 2011 that were methodologically superior and whose outcomes were pertinent to teaching and education in emergency medicine (EM). Methods A search of the English language literature in 2011 querying PubMed, Scopus, Education Resources Information Center (ERIC), and PsychInfo identified EM studies that used hypothesis‐testing or observational investigations of educational interventions. Six reviewers independently ranked all publications based on 10 criteria, including four related to methodology, that were chosen a priori to standardize evaluation by reviewers. This method was used previously to appraise medical education published in 2008, 2009, and 2010. Results Forty‐eight educational research papers were identified. Comparing the literature of 2011 to that of 2008 through 2010, the number of published educational research papers meeting the criteria increased over time from 30, to 36, to 41, and now to 48. Five medical education research studies met the a priori criteria for inclusion as exemplary and are reviewed and summarized in this article. The number of funded studies remained fairly stable over the past 3 years, at 13 (2008), 16 (2009), 9 (2010), and 13 (2011). As in past years, research involving the use of technology accounted for almost half (n = 22) of the publications. Observational study designs accounted for 28 of the papers, while nine studies featured an experimental design. Conclusions Forty‐eight EM educational studies published in 2011 and meeting the criteria were identified. This critical appraisal reviews and highlights five studies that met a priori quality indicators. Current trends and common methodologic pitfalls in the 2011 papers are noted.